“You’ve got children haven’t you…?”: Involuntary childlessness as a neglected aspect of therapist diversity in the professional context - Stokley, Martin; Sanders, Val (European Journal for Qualitative Research in Psychotherapy, 2020)
In a previous article we detailed the findings of a qualitative research project into the lived experience of qualified involuntary childless therapists and showed how this connected to work with clients in the therapy room. The project also examined the experience of involuntary childless therapists in relation to the wider profession and counselling theory (areas which are missing from the existing literature). This current article presents these findings and discusses their implications. Five participants completed a semi-structured interview. Interpretative Phenomenological Analysis was used to analyse interview transcripts and draw out aspects of the lived experience of involuntary childless therapists. A variety of experience in the professional context was found. For some participants supervision was a safe space to discuss their childlessness and for others it was a place of alienation, anxiety and potential judgement. The participants tended to find themselves feeling on the edge of the therapy world and the issue of microaggressions around childlessness is discussed. In relation to a therapist developing their theoretical approach the participants’ experiences demonstrate the need for reflexivity around how childlessness may impact the process. This article highlights the importance of parental status being recognised as a significant and often unacknowledged aspect of difference and diversity for therapists.